2017
DOI: 10.3892/mmr.2017.6480
|View full text |Cite
|
Sign up to set email alerts
|

Sclareol inhibits cell proliferation and sensitizes cells to the antiproliferative effect of bortezomib via upregulating the tumor suppressor caveolin-1 in cervical cancer cells

Abstract: The anticancer effect of sclareol has long been reported, however, the exact mechanisms underlying the antitumorigenic effect of sclareol in cervical carcinoma remain to be fully elucidated. The present study analyzed cell proliferation and cell apoptosis by MTT and FITC-Annexin V assays. The protein levels of caveolin-1 (Cav-1) and copper-zinc superoxide dismutase (SOD)1 were determined by western blotting, and the interaction of Cav1 and HSC70 was investigated by co-immunoprecipitation experiments. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The bioactivities of some compounds of the essential oil identified from the leaves of V. rotundifolia in this study have been documented in previous studies [ZHANG et al, 2017] .…”
Section: Resultssupporting
confidence: 73%
“…The bioactivities of some compounds of the essential oil identified from the leaves of V. rotundifolia in this study have been documented in previous studies [ZHANG et al, 2017] .…”
Section: Resultssupporting
confidence: 73%
“…It has been reported that genetic changes of Cav1 might modify the risk for breast cancer,151 and Cav1 acts both as a tumor suppressor as well as an oncogene, and plays a key role in breast cancer tumorigenesis 152. In addition to breast cancer carcinogenic process, Cav1 is also associated with lung cancer,153,154 colorectal cancer,155 gastric cancer,156,157 cervical cancer,158 hepatocellular carcinoma,159 pancreatic cancer,160 bladder cancer,161 pulmonary hypertension,162164 virus infection,165,166 cardiovascular disease,167,168 diabetes mellitus,169 nanomedicines endocytosis170 and lipodystrophy 171. Besides, it has been reported that caveo-lin-2 (Cav2) can also mediate the initiation and development of breast cancer 26…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Although several labdane diterpenoids such as sclareol, coronarin D, andrographolide, and selected hispanolone derivatives have been described to exhibit potent antitumor activities via induction of apoptosis (Mahaira et al, 2011; Lim et al, 2012; Traves et al, 2013; Mishra et al, 2015; Mota et al, 2015; Wang et al, 2015; Zhang et al, 2017), few data have been reported regarding their role on cell migration. Indeed, to the best of our knowledge, this is the first study describing the anti-invasiveness properties of hispanolone derivatives on glioblastoma tumors.…”
Section: Discussionmentioning
confidence: 99%